NIEKTÓRE ASPEKTY TZW. AUTENTYCZNOŚCI TEKSTÓW AKTÓW NORMATYWNYCH - Wojciechowski, Maciej (Wydział Prawa i Administracji UAM, 2008)
The article is devoted to one of the problems of issuing normative acts, namely the feature of their authenticity that is ascribed to officially published acts by the doctrine. In the first part, the author analyses the concept of authenticity at the level of various types of language considering its semiological aspect related to real objects e.g. works of art. In the second part, the historical evolution of promulgating the law is presented from the function of announcing the content of the law to one of the formal criteria for the binding force of law. In the third part of the article, modern means of obtaining information about the content of legal standards is discussed and the informational value of authentic texts is evaluated. In further parts, a typology of errors in officially published normative acts is discussed and set in the context of historical and present legal status with a suggestion de lege ferenda. The article ends with a proposition of normative changes in the way of promulgating the law that is supposed to include the Internet and their meaning in the context of the issues raised in the second part of the article.
SELECTED ASPECTS OF AUTHENTICITY OF THE TEXTS OF NORMATIVE ACTS